Underwater Wireless Sensor Networks: Routing Issues and Future Challenges - Muhammad, Ayaz; Azween, Abdullah (2009)
With the advancements of acoustic modem technology that supports better data rates with reliable communications, current research focuses on algorithms those can support such technology in a better way. During the last two decades, many protocols suggested in order to handle the adverse environment of underwater communications. This continued research results in improved performance as compare to initial communication systems. But still underwater issues like limited bandwidth, high propagation delays and 3-D topology as well as power constraints of the sensor nodes are challenges for the successful routings. A series of survey papers provide an excellent comparison of such algorithms and different networking challenges during the current decade, but still a lot left to investigate. In this paper we will explore the developments of some of the important routing algorithms, and a survey with different comparisons, those have been proposed for the partially connected underwater environments. In addition, at the end we will give some future directions, which can be helpful in order to construct the algorithms for such environments.